Analysis Of Factors Influencing Consumer Decisions In Buying Trademarked Tempe In Langsa City - Tika, Nuri Hidayah; Alham, Fiddini; Rosalina, Rosalina (Sharia Agribusiness Journal, 2024)
ABSTRACTThis study aims to analyze the factors that influence consumer decisions to purchascing trademarked tempeh in Langsa City. The independent variables used in this research are price, brand image, quality and packaging. The dependent variable  is the consumers’ decision to buy trademarked tempeh. The sampling technique was detrermined used the nonprobability sampling method, namely, the accidental sampling method of 60 respondents. Primary and secondary data were used for a quantitative descriptive approach. The data analysis included multiple linear regression analyses. The results show that  price and quality variables (X1 and X3) have a significant effect on consumer decisions in buying trademarked tempeh, whereas brand image and packaging variables (X2 and X4) do not have a significant effect on consumer decisions in buying trade branded tempeh.Keywords: tempeh; consumer decisions; price; brand image; quality; packaging ABSTRAKPenelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi keputusan konsumen dalam membeli tempe bermerek di Kota Langsa. Variabel bebas yang digunakan dalam penelitian ini adalah harga, citra merek, kualitas dan kemasan. Variabel terikatnya adalah keputusan konsumen dalam membeli tempe bermerek. Teknik pengambilan sampel menggunakan metode nonprobability sampling yaitu metode accidental sampling dengan jumlah responden sebanyak 60 orang. Data primer dan sekunder digunakan untuk pendekatan deskriptif kuantitatif. Analisis data yang digunakan adalah analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa variabel harga dan kualitas (X1 dan X3) berpengaruh signifikan terhadap keputusan konsumen dalam membeli tempe bermerek, sedangkan variabel citra merek dan kemasan (X2 dan X4) tidak berpengaruh signifikan terhadap keputusan konsumen dalam membeli tempe bermerek.Kata Kunci: tempe; keputusan konsumen; harga; citra merek; kualitas; kemasan